PEMBELAJARAN GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR MATERI KEMERDEKAAN MENGEMUKAKAN PENDAPAT - Sugi, Sugi (Forum Ilmu Sosial, 2016)
The aim of research to find out the learning outcome of material freedom of expression through the study group investigation A class VII SMP Negeri 3 Temanggung 2nd semester of the school year 2014/2015. Research in class VII A of 32 learners. Source data from the primary data source and sekunder.Pengumpulan data using test techniques to determine the results of study and observation sheet form non-test to determine the learning process. Class Action Research conducted two siklus.Hasil study were analyzed using descriptive analysis of comparative continued reflection, the learning process with a qualitative descriptive analysis continued reflection. From the initial conditions to the first cycle increased learning outcomes with an average value of 69 to 78, an increase of 13.04 percent. In the two cycle average value of 86 increased 24.65 percent from the initial conditions. There is an increase in the activity of learners and teachers. Group investigation concluded that the learning materials improve learning outcomes freedom of expression of class VII A SMP Negeri 3 Temanggung 2nd semester of the school year 2014/2015